Analysis of Efficiency and Effectiveness of Realization of Regional Revenue and Expenditure Budget at Bpkad Surabaya - Aprillia, Natasya Putri; Andayani, Sari (Jurnal Ekonomi Balance, 2022)
The purpose of this study was to analyze and determine the level of quality of local government financial performance as measured by the ratio analysis of the efficiency of regional spending and the effectiveness of regional income on the realization of the Surabaya City Budget. This research uses descriptive quantitative research. The data used in this realization research is secondary data in the form of 2017-2020 regional budget income and expenditure reports obtained from Badan Pengelolaan Keuangan Dan Aset Daerah Kota Surabaya, using the financial ratio analysis method of regional expenditure efficiency and the effectiveness of local revenue. The results show that the financial performance of the Surabaya City Government at the level of regional expenditure efficiency during the 2017-2020 fiscal year period with criteria is quite efficient, because the management of the regional budget does not exceed 100%.The financial performance of the Surabaya City Government at the level of effectiveness of local revenue during the 2017-2020 fiscal year period with very effective criteria, where the percentage of the effectiveness ratio is above 100% on average